Alive! : daily devotionals for young people - Christian, S. Rickly (Scott Rickly) (Grand Rapids, Mich. : Zondervan Pub. House ; Wheaton, Ill. : Campus Life Books, 1985)
Daily readings for the high schooler, using Scripture as a springboard to reflect on God and Christianity in school life, dating, sex, parental relations, fears, peer pressure, etc.
Keywords: Teenagers -- Prayers and devotions; Devotional calendars; Prayer books and devotions; Christian life